Development of an Administrative Data-Based Frailty Index for Older Adults Receiving Dialysis. Issue 9 (29th September 2022) - Hall, Rasheeda K.; Morton, Sarah; Wilson, Jonathan; Kim, Dae Hyun; Colón-Emeric, Cathleen; Scialla, Julia J.; Platt, Alyssa; Ephraim, Patti L.; Boulware, L. Ebony; Pendergast, Jane
Visual Abstract: Abstract : Key Points: Accounting for comorbidity, this frailty index demonstrates an independent association with mortality and hospitalizations. This frailty index has potential application for both observational studies and population health management. Background: Frailty is present in ≥50% of older adults receiving dialysis. Our objective was to a develop an administrative data–based frailty index and assess the frailty index's predictive validity for mortality and future hospitalizations. Methods: We used United States Renal Data System data to establish two cohorts of adults aged ≥65 years, initiating dialysis in 2013 and in 2017. Using the 2013 cohort (development dataset), we applied the deficit accumulation index approach to develop a frailty index. Adjusting for age and sex, we assessed the extent to which the frailty index predicts the hazard of time until death and time until first hospitalization over 12 months. We assessed the Harrell's C-statistic of the frailty index, a comorbidity index, and jointly. The 2017 cohort was used as a validation dataset. Results: Using the 2013 cohort ( n =20, 974), we identified 53 deficits for the frailty index across seven domains: disabilities, diseases, equipment, procedures, signs, tests, and unclassified. Among those with ≥1 deficit, the mean (SD) frailty index was 0.30 (0.13), range 0.02–0.72. Over 12 months, 18% ( n =3842) died, and 55% ( n =11, 493) experienced a hospitalization. Adjusted hazard ratios for each 0.1-point increase in frailty index in models of time to death and time to first hospitalization were 1.41 (95% confidence interval, 1.37 to 1.44) and 1.33 (95% confidence interval, 1.31 to 1.35), respectively. For mortality, C-statistics for frailty index, comorbidity index, and both indices were 0.65, 0.65, and 0.66, respectively. For hospitalization, C-statistics for frailty index, comorbidity index, and both indices were 0.61, 0.60, and 0.61, respectively. Data from the 2017 cohort were similar. Conclusions: We developed a novel frailty index for older adults receiving dialysis. Further studies are needed to improve on this frailty index and validate its use for clinical and research applications.